2017
DOI: 10.4236/jdm.2017.73013
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Adherence to Anti-Diabetic Therapy in Pregnant Women with Diabetes: Health Care Workers’ Perspectives

Abstract: Global prevalence of hyperglycaemia in pregnancy in women of 20 -49 years was estimated to be 16.9% and affecting 21.4 million live births, in 2013, 90% of which occurred in developing countries. The cornerstone of anti-diabetic therapy is diet, physical activity and medications. The study utilized a qualitative descriptive design using key informant interviews from August 2016 to November 2016 to explore challenges of adherence to anti-diabetic therapy in pregnant women with diabetes at a central hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The impact of social support and the potential to the use of a support network in improving diabetes medication adherence among pregnant women especially in low-and middle-income settings is highly recommended based on findings from this review. Some papers also showed that patients with high socioeconomic status (SES) had higher adherence rates [20,25,27], while another study showed the opposite [20]. Women with low socioeconomic status were often nonadherent due to financial constraints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of social support and the potential to the use of a support network in improving diabetes medication adherence among pregnant women especially in low-and middle-income settings is highly recommended based on findings from this review. Some papers also showed that patients with high socioeconomic status (SES) had higher adherence rates [20,25,27], while another study showed the opposite [20]. Women with low socioeconomic status were often nonadherent due to financial constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant medications used in the management of gestational diabetes according to the papers reviewed were insulin [18,[20][21][22][23][24] and metformin [19,21,22,25]. Besides medications, adherence to lifestyle/behaviours like self-monitoring of blood glucose levels, dietary therapy, and physical activity were considered [18,20,[22][23][24][25][26][27][28]. Self-report measures were the recorded means of estimating adherence [18-26, 28, 29].…”
Section: Types Of Medications and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Interviews were thematically analyzed and findings were reported as themes and categories. Findings of the key informant interviews have already been published [14].…”
Section: Qualitative Phasementioning
confidence: 99%
“…Health education should be customised to suit individual patient needs. More recommendations from the findings of the study have been published elsewhere [42,43]. Strict adherence to healthy lifestyle habits must be advocated in health policies particularly in developing countries where access to and quality of health care are problems.…”
Section: Implications Of the Findingsmentioning
confidence: 95%